RETRACTED ARTICLE: Adaptive Theory Approach In Leadership: A Guide to Educational Management System and Mechanisms - Mallillin, Leovigildo Lito D. (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2022)
This paper has been retracted. The study aims to examine the process of adaptive theory in leadership as a guide to educational management mechanisms in terms of qualities and characteristics of leadership, challenges of leadership, strengthening accountability in leadership, the problem-solving process in leadership, and the decision-making process in leadership. The study employs a quantitative research design. It adopts the immersive pedagogical method in education and leadership mechanisms that constitutes challenges in the educational leadership theory and mechanism. The study employs a convenient sampling technique. The study comprised thirty-two (32) respondents only. Results show that qualities and characteristics of leadership foresee the change and understanding of the process in the educational system, understand the persistence and process of the pressure gradually. Willingness to handle the situation and leadership challenges focus on effective teachers and effective leaders, the principles and competency in learning, innovate change for leaders to enact new resources in the educational system in creative challenges for new development realities and solutions to work. Strengthening accountability in leadership, ensuring precautionary measures in a better relationship in school organization and educational system and innovating change and behavior in the educational system, and diagnosing the symptoms of the situation to include the techniques in solving the expected and decision-making process in leadership style in the educational system. Finally, it explores the adaptive theory application in leadership as a guide in the educational management system and mechanisms to provide suggestions and follow-up for further study and development.